Evaluasi Terapi Insulin pada Penderita Diabetes Mellitus Gestasional di RSUP Dr. Soeradji Tirtonegoro Klaten Periode Oktober 2014-Oktober 2017 - Ayu Lestari Cahyaningsih; Surya Amal (University Of Darussalam Gontor, 2019)
Gestasional diabetes mellitus is a disease of diabetes which occurs during pregnancy, and it needs attention because several impact that can be caused. This study was conducted to evaluate insulin therapy by reviewing patient characteristics and patterns of insulin use in hospitalized patients in dr. Soeradji Tirtonegoro Klaten which diagnosed gestasional diabetes mellitus and the effectiveness of insulin therapy by blood sugar measurement before and after insulin therapy. This type of research is descriptive which is done retrospectively. Population in this study were 16 patients with sample that fulfilled the inclusion criteria of 9 patients. The result of research indicated that more than half of Gestasional DM patients were over 30 years old, data also indicated 66,67% of Gestasional DM patients were not working, 55,56% patients had a highly educated, 88,89% patients treated for less than 7 days, 77,78% patients had Gestasional DM at 3rd trimester, and 55,56% patients underwent caesarea section. Insulin therapy was given by 3 types of insulin there are, rapid-acting insulin (Novorapid), long-acting insulin (Levemir), and mixed-action insulin (Novomix). The effectiveness of insulin therapy has been evaluated based on decreased blood glucose levels before and after insulin use. Statistically it can be concluded that insulin therapy in Gestasional DM patient can significantly decrease patient’s blood glucose level